Translocation of botulinum neurotoxin serotype A and associated proteins across the intestinal epithelia. (15th February 2015) - Lam, Tina I.; Stanker, Larry H.; Lee, Kwangkook; Jin, Rongsheng; Cheng, Luisa W.
Summary: Botulinum neurotoxins (BoNTs) are some of the most poisonous natural toxins. Botulinum neurotoxins associate with neurotoxin‐associated proteins (NAPs) forming large complexes that are protected from the harsh environment of the gastrointestinal tract. However, it is still unclear how BoNT complexes as large as 900 kDa traverse the epithelial barrier and what role NAPs play in toxin translocation. In this study, we examined the transit of BoNT serotype A (BoNT/A) holotoxin, complex and recombinantly purified NAP complex through cultured and polarized Caco‐2 cells and, for the first time, in the small mouse intestine. Botulinum neurotoxin serotype A and NAPs in the toxin complex were detectable inside intestinal cells beginning at 2 h post intoxication. Appearance of the BoNT/A holotoxin signal was slower, with detection starting at 4–6 h. This indicated that the holotoxin alone was sufficient for entry but the presence of NAPs enhanced the rate of entry. Botulinum neurotoxin serotype A detection peaked at approximately 6 and 8 h for complex and holotoxin, respectively, and thereafter began to disperse with some toxin remaining in the epithelia after 24 h. Purified HA complexes alone were also internalized and followed a similar time course to that of BoNT/A complex internalization. However, recombinant HA complexes did not enhance BoNT/A holotoxin entry in the absence of a physical link with BoNT/A. We propose a model for BoNT/A toxin complex translocation whereby toxin complex entry is facilitated by NAPs in a receptor‐mediated mechanism. Understanding the intestinal uptake of BoNT complexes will aid the development of new measures to prevent or treat oral intoxications.